Optimizing invesment decisions: A comparative analysis of fundamental and technical approaches - Amraini, Amraini; Muchran, Muchriana; Mira, Mira (Universitas Ahmad Dahlan, 2025)
This study discusses the comparison between using technical analysis independently and combining fundamental analysis with technical analysis in optimizing stock investment decision-making. The data used is secondary data from LQ45 stocks during the period of February to July 2024. Technical analysis in this study uses the Stochastic RSI indicator, while fundamental analysis refers to the Price to Book Value (PBV) ratio. The results show using technical analysis has an accuracy rate of 92% with a profit of 16.224, which is higher than the combination of both analyses which recorded an accuracy of 87% and a profit of 5.999. Nevertheless, the combined strategy is proven to be more effective in reducing investment risk, making it still relevant for investors who focus on long-term security. This study is important because in investment practice, market participants often face confusion in choosing the most suitable analytical approach. By empirically comparing the two strategies, and this study provides insights that can help investors adjust their strategies based on their goals, risk tolerance, and investment horizon, so that the decisions made are more targeted and measurable.